2007
DOI: 10.1371/journal.pone.0000508
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Locus Global DNA Barcode for Land Plants: The Coding rbcL Gene Complements the Non-Coding trnH-psbA Spacer Region

Abstract: BackgroundA useful DNA barcode requires sufficient sequence variation to distinguish between species and ease of application across a broad range of taxa. Discovery of a DNA barcode for land plants has been limited by intrinsically lower rates of sequence evolution in plant genomes than that observed in animals. This low rate has complicated the trade-off in finding a locus that is universal and readily sequenced and has sufficiently high sequence divergence at the species-level.Methodology/Principal FindingsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,270
6
29

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,251 publications
(1,356 citation statements)
references
References 34 publications
51
1,270
6
29
Order By: Relevance
“…2011). Others have reported low resolution in rbcL because it is known to have insufficient nucleotide sequence variability to distinguish among closely related species (Kress & Erickson, 2007; Newmaster, Grguric, Shanmughanandhan, Ramalingam, & Ragupathy, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…2011). Others have reported low resolution in rbcL because it is known to have insufficient nucleotide sequence variability to distinguish among closely related species (Kress & Erickson, 2007; Newmaster, Grguric, Shanmughanandhan, Ramalingam, & Ragupathy, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Three parameters were used to compare intraspecific divergence (Lahaye et al, 2008;Meyer and Paulay, 2005): (i) the mean of all intraspecific distances within species with at least two individuals; (ii) the "mean theta," where theta is the average pairwise distance calculated within species to eliminate biases associated with different samplings among species; and (iii) the average coalescent depth, that is, the maximum distance within each species. Wilcoxon signed-rank tests were performed to compare intraspecific variability and the interspecific variability of every pair of barcodes following Kress and Erickson (2007). The barcoding gaps were evaluated by comparing the distribution of interspecific/intraspecific divergence.…”
Section: Resultsmentioning
confidence: 99%
“…However, the NJ tree indicated that the species with different higher-level phylogenies, such as the subgenus and the genus (the outgroup), can be distinguished. Numerous other studies also suggested that rbcL is only suitable for DNA barcode at the genus level (and above) (Kress and Erickson, 2007;Newmaster et al, 2006;Sass et al, 2007).…”
Section: Applicability Of the Candidate Chloroplast Dna Barcodesmentioning
confidence: 99%
See 2 more Smart Citations